2008
DOI: 10.7205/milmed.173.12.1180
|View full text |Cite
|
Sign up to set email alerts
|

Validation of Lower Limb Surrogates as Injury Assessment Tools in Floor Impacts due to Anti-Vehicular Land Mines

Abstract: The aim of this study was to assess the ability of lower limb surrogates to predict injury due to floor/foot plate impact in military vehicles during anti-vehicular land mine explosions. Testing was conducted using two loading conditions simulated to represent those conditions created in the field. The lower condition was represented by a 24-kg mass impactor with a velocity of 4.7 m/s. The higher loading condition was represented by a 37-kg mass impactor with a velocity of 8.3 m/s. Two biomechanical surrogates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 11 publications
2
22
0
Order By: Relevance
“…Previous studies have found ATD to cadaveric ratios between 1.8 and 2.8. 12,13 This study attained a ratio of ATD to cadaveric forces of up to 2.8, which agrees with these previous studies. We found that a 10% risk of tibia injury would register as an ATD force of ϳ12.6 kN, which is more than double the currently used limit of 5.4 kN, as measured with an ATD.…”
Section: Discussionsupporting
confidence: 92%
“…Previous studies have found ATD to cadaveric ratios between 1.8 and 2.8. 12,13 This study attained a ratio of ATD to cadaveric forces of up to 2.8, which agrees with these previous studies. We found that a 10% risk of tibia injury would register as an ATD force of ϳ12.6 kN, which is more than double the currently used limit of 5.4 kN, as measured with an ATD.…”
Section: Discussionsupporting
confidence: 92%
“…Experimental and computational models of blast, as well as surrogate (b) Experimental models of blast injury (i) Scaled-blast simulations The test rig for occupant safety system (TROSS) is a vehicle floor simulant, which uses scaled detonations to provide the same blast parameters to a vehicle occupant as those occurring in an underbelly vehicle blast of 2 -10 kg of TNT [26]. This has been used as a test-bed to evaluate the biofidelity of surrogates in AV-mine blast and to define input loading conditions for controlled laboratory experiments with cadavers or surrogates [30][31][32]. There is no scientific literature presenting cadaveric testing with TROSS.…”
Section: Current Clinical Focusmentioning
confidence: 99%
“…The H-III has been shown to overestimate the axial tibial force induced in UBB4,5,17,22,26 and therefore, to protect the H-III from damage, the target average peak velocity was 8.7 m/s at an average time to peak velocity of 10.8 ms, compared to an average velocity and time to peak velocity of 12.7 m/s and 8.8 ms in the PMHS tests. The MiL-Lx was exposed to the same threat as the H-III to allow for comparisons between them.…”
Section: Discussionmentioning
confidence: 98%